2019
DOI: 10.3390/s19040815
|View full text |Cite
|
Sign up to set email alerts
|

3D Path Planning for the Ground Robot with Improved Ant Colony Optimization

Abstract: Path planning is a fundamental issue in the aspect of robot navigation. As robots work in 3D environments, it is meaningful to study 3D path planning. To solve general problems of easily falling into local optimum and long search times in 3D path planning based on the ant colony algorithm, we proposed an improved the pheromone update and a heuristic function by introducing a safety value. We also designed two methods to calculate safety values. Concerning the path search, we designed a search mode combining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 44 publications
(62 reference statements)
0
16
0
1
Order By: Relevance
“…In Table 6, additional information from previous research related to PSO is shown. Ant colony optimization (ACO) is usually studied under varying network environments, such as grid network and Voronoi diagram [107][108][109][110][111][112][113][114][115][116][117][118][119]. Few papers, likewise, researched GA with ACO and coordinate system [120].…”
Section: Refmentioning
confidence: 99%
“…In Table 6, additional information from previous research related to PSO is shown. Ant colony optimization (ACO) is usually studied under varying network environments, such as grid network and Voronoi diagram [107][108][109][110][111][112][113][114][115][116][117][118][119]. Few papers, likewise, researched GA with ACO and coordinate system [120].…”
Section: Refmentioning
confidence: 99%
“…ACO-based coordinated path planning for multi-UAV networks under threat conditions is discussed in [ 42 ]. Three-dimensional path planning for robots to avoid local maxima is elaborated in [ 43 ]. Parallel genetic algorithm-based multi-UAV path and trajectory is discussed in [ 44 ].…”
Section: Related Workmentioning
confidence: 99%
“…Map representation is a cartographic method to express the geographical height, topography and surface features on the plane in various ways by means of graphics with the aid of natural language. Extensive research has implemented a variety of 3D environment modeling map representation methods, including digital point cloud method [23], [24], triangular grid map method [25], [26], traditional node map method [27], [28], and square grid map method [29]- [31] and so on. The square grid method is a kind of map representation method with grid as cartographic unit, which reflects the characteristics of cartographic objects.…”
Section: D Coarse-fine Scale Map Model and Coarse Scale Optimal mentioning
confidence: 99%